Pneumothorax during laparoscopic repair of giant paraesophageal hernia - Ranvinder Kaur; Santvana Kohli; Aruna Jain; Homay Vajifdar; Raghavendra Babu; Deborshi Sharma (Wolters Kluwer Medknow Publications, 2011)
Giant paraesophageal hernia is an uncommon morbid disorder which may present a risk of catastrophic complications and should be repaired electively as soon as possible. Laparoscopic fundoplication is the mainstay of surgical management of this disorder due to several advantages such as lower post-operative morbidity and pain. We report a case of a 70-year-old patient with a giant paraesophageal hernia, who developed subcutaneous emphysema with pneumothorax during laparoscopic fundoplication. Early diagnosis was possible by close clinical evaluation and simultaneous monitoring of end-tidal carbon dioxide levels and airway pressures. Although positive end-expiratory pressure application is an effective way of managing pneumothorax secondary to the passage of gas into the interpleural space, insertion of an intercostal drain may be used in an emergent situation.